Electrical Conductivity and Electronic Absorption Spectra of CaTiO3Doped with Ga2O3 - Hanafi, Z.M.; Hammad, F.F.; Salama, A.H. (Asian Journal of Chemistry, 2010)
The temperature dependence of the electrical conductivity of pure CaTiO3 and that containing Ga2O3 dopant with different concentration was investigated between 291 and 773°C. The conductivity in this temperature range varied widely with the percentage change in the concentration of dopant. In the lower temperature range, no variation of conductivity was observed. This was interpreted as impurity controlled conduction. In the higher temperature range, all doped investigated samples, as wen as pure CaTiO3 exhibited nearly the same shape and the same value of activation energy. This behaviour was attributed to ionization energy present and/or change from cubic to orthorhombic modification. The optical absorption spectra indicate two absorption maxima (ΔE1 and ΔE2). The values of ΔE1 depend on the lattice defects present; ΔE2 represents the gap width of CaTiO3. It was observed that change of Δe2 due to additives is very slight; these changes may be attributed to the variation in the volume of unit cell of the doped samples.